Peran Pendidikan Agama Islam (PAI) Dalam Stres Akademik Siswa SMA Muhammadiyah Banyuresmi - Wahidah, Evita Yuliatul; Barokah, Barokah (STAI Al-Musaddadiyah Garut, 2024)
Starting from academic anxiety about the phenomenon of phenomena that occur in the world of education. Quoted from page suara.com there was a 13-year-old student who committed suicide using a towel after doing homework (homework) with his mother, it was known that previously the child complained a lot to his parents because there was too much homework (homework) that stressed him.The aim of this research is to describe academic factors in Muhammadiyah high schools, describe the symptoms of academic stress among Muhammadiyah high school students, describe various types of academic stress in Muhammadiyah high school students, and describe the role of Islamic religious education in the academic stress of Muhammadiyah high school students Banyuresmi.The method used in this research uses a qualitative approach using descriptive methods. As for the definition of descriptive according to Sugiyono, quoted by Melinda Rizky, namely a method that functions to describe or provide an overview of an object being studied through data or samples that have been collected as they are without carrying out analysis to make conclusions that apply to the general public. The results of this research show that Islamic religious education has an important role in students' academic stress, in the form of preventive measures by identifying things that are likely to cause students to experience academic stress, after which this is done, an initial conclusion can be drawn. The results of this study show that Islamic Religious Education (PAI) has an important role in students' academic stress, in the form of preventive measures by identifying things that are likely to make students experience academic stress, after which an initial conclusion is drawn by PAI teachers such as when there are too many tasks, then after it is known that when there are too many tasks will make it stressful, PAI teachers reduce in assigning assignments. Curative steps or treatment are carried out by; Report to the student's homeroom teacher regarding their condition, coordinate with the counseling guidance teacher to conduct a home visit, tell the student to always maintain the quality of sleep and eating because it affects learning activities, always encourage them to always maintain the five-time prayer, dhikr to Allah, and be grateful as a solution to all problems, always motivate students to develop. Keywords: Academic Stress, Role of Islamic Religious Education, Stres High School Student